Analyzing the impact of psychological capital and work pressure on employee job engagement and safety behavior - Saleem, Muhammad Shoaib; Isha, Ahmad Shahrul Nizam Bin; Benson, Chizubem; Awan, Maheen Iqbal; Naji, Gehad Mohammed Ahmed; Yusop, Yuzana Binti (Frontiers in Public Health, 2022)
The construction industry primarily focuses on building and infrastructure construction, development, demolition, renovation, maintenance, and repair. The capacity of the sector to overcome dangerous situations onsite in any project and work effectively is highly dependent on effective safety performance. Furthermore, having a proper understanding of the impacts of psychological Capital, Work Pressure, Work Engagement, and Safety Participation would improve workers' safety performance in the Malaysian construction industry. Data was gathered through a random sample of workers in the Malaysian construction industry, including administrative and field workers in various departments in the country's six regions. The workers were given a total of 500 questionnaires, of which 345 were returned to the team of researchers. Based on the data analysis, there is an effective interaction between the factors tested toward safety performance. According to findings, psychological capital positively and significantly affected workers' work engagement. Also, work engagement greatly impacted both workers' safety performance outcomes. Also, as expected, worker pressure was found to significantly and negatively affect workers' safety performance. Additionally, the study has contributed to our understanding of improving and ensuring workplace safety performance by encouraging optimal work organization and worker participation in safety. Also, the research advised the construction industry to reduce work pressure which will minimize Psychological Capital and Increase worker strength to follow safety performance in their duties.